2020
DOI: 10.1128/aem.01847-20
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Microbial Negative Correlations into Positive Correlations by Saccharomyces cerevisiae Inoculation during Pomegranate Wine Fermentation

Abstract: The application of starter is a common practice to accelerate and steer pomegranate wine fermentation process. However, the use of starter needs to better understand the effect of the interaction between starter and native microorganisms during alcoholic fermentation. In this study, high-throughput sequencing combined with metabolite analysis were applied to analyze the effect of commercial Saccharomyces cerevisiae inoculation on the native fungal community interaction and metabolism during pomegranate wine fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Isoamyl alcohol and 2-phenylethanol were the alcohols found in highest amounts, while the most abundant esters were isoamyl acetate and phenylethyl-acetate (among acetates), ethyl hexanoate, and octanoate and decanoate (among ethyl esters). Similar volatile profiles were reported in the literature [27,36,41,42]. Several significant differences were however observed in the levels of volatile compounds, due to both Cultivar and Yeast variables.…”
Section: Volatile Compoundssupporting
confidence: 88%
“…Isoamyl alcohol and 2-phenylethanol were the alcohols found in highest amounts, while the most abundant esters were isoamyl acetate and phenylethyl-acetate (among acetates), ethyl hexanoate, and octanoate and decanoate (among ethyl esters). Similar volatile profiles were reported in the literature [27,36,41,42]. Several significant differences were however observed in the levels of volatile compounds, due to both Cultivar and Yeast variables.…”
Section: Volatile Compoundssupporting
confidence: 88%
“…S. cerevisiae is one of the most important species in fermented foods and contributes to the production of alcohols and esters [47]. In winemaking, S. cerevisiae is widely used as a starter culture [48]. Moreover, inoculation with S. cerevisiae has been recommended to enhance flavor complexity and microbial community stability.…”
Section: Isolation Of Geosmin-inhibiting Microorganisms From Daqumentioning
confidence: 99%
“…Moreover, inoculation with S. cerevisiae has been recommended to enhance flavor complexity and microbial community stability. For example, pomegranate wine fermentation with S. cerevisiae inoculation transformed the negative correlations into positive correlations among the fungal communities [48]. Inoculated S. cerevisiae can suppress wild microflora, determining the starter's ability to dominate the process [49].…”
Section: Isolation Of Geosmin-inhibiting Microorganisms From Daqumentioning
confidence: 99%
“…Kioroglou et al found that oak barrel aging had no significant effect on microbial diversity during the wine aging process, but did alter the population structure and composition of fungi and bacteria (Ma et al, 2018). Using highthroughput sequencing technology, Wang et al (2020b) found that inoculation with starter cultures altered the interactions and metabolism of primitive fungal communities during pomegranate wine fermentation. Therefore, not only the positive characteristics of the starter culture, but also the interaction between the starter culture and the original flora should be considered in starter culture inoculation (Kioroglou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, not only the positive characteristics of the starter culture, but also the interaction between the starter culture and the original flora should be considered in starter culture inoculation (Kioroglou et al, 2020). Wang et al (2020b) analyzed the traditional fungal resources…”
Section: Introductionmentioning
confidence: 99%